A spectacle of corruption a novel - Liss, David 1966- (Random House, an imprint of the Random House Publishing House, 2004)
"I sentence you, Mr. Weaver, to be hanged for the most horrible crime of murder." Hearing that judicial decree, Benjamin Weaver--former pugilist, current "thief-taker," and future master of disguise--begins one of the sorriest days of his life. And things will only get worse. Tossed into London?s notorious Newgate Prison, Weaver employs his considerable energy and guile (plus tools slipped to him by a mysterious admirer at his trial) to escape--naked--into the city's filthy streets. But then, he risks recapture by trying to figure out who framed him for slaying labor agitator Walter Yate, and why.